GAMMA RADIATION SHIELDING POTENCY OF B2O3–TEO2–BAO-DY2O3 GLASS-CERAMIC (Jurnal Teknologi (Sciences & Engineering), 2025)
Ionizing radiation Teletherapy Ionizing radiation is used in medical imaging, radiation therapy and research, which requires high-performance shielding materials to be safe. Ionizing radiations are very dangerous to the health and this is dependent on the amount of dose and the duration of exposure. Considering this, it is important to develop shielding materials. In this work, a novel family of glass systems was synthesized (50-x)B 2 O 3 -25TeO 2 -25BaO-xDy 2 O 3 with 0 mol % x 1.25 mol %. Partially crystallized glass ceramic (GC) samples were obtained by undergoing a stepwise heating processing: annealing at 570 0 C and heating at 6201655 0 C for 2 hours forming glasses. XRD structural analysis proved crystallinity as well as multi-phased. High Dy 2 O 3 content also increased the G C density to 4.994 g / cm 3 and reduced molar volume to 24.8376 cm 3 / mol as well as led to a rise in elastic properties such as longitudinal velocity, shear velocity, longitudinal elastic modulus and shear elastic modulus as a reflection of the increased density and bond strength. The shielding effectiveness of gamma rays against sources of 137Cs and 60Co at 0.662, 1.173, and 1.333 MeV were tested by a NaI(Tl) detector. As concentration of Dy2O 3 increased, the mass attenuation coefficient (MAC) increased in this order BBTDGC1.25 > BBTDGC1 > BBTDGC0.75 > BBTDGC0. The BBTDGC1.25 sample had the best MAC and worst half-value layer (HVL) tenth-value layer (TVL) and mean free path (MFP).